A STUDY OF HOAXES SPREAD IN DIGITAL REPUTABLE JOURNALISM MEDIA - Diana Aslamiyyah; Norma Desvia Rahman; Queenadia Syahrani (Bajang Institute, 2021)
Currently, it is still possible to find the spread of fake news or hoaxes on social media, especially supported by the development of communication technology that can help the public access all news through online sites. People can easily find and access news through online media, whether well-known media or not. The well-known news media also does not guarantee that the news provided is free from hoaxes. Therefore, this study aims to explain and provide an overview of the pattern of hoax spread in digital media that has an impact on media reputation. This research method uses an approach by finding and collecting data which is then analyzed based on the theory of hoax patterns according to the experts used by researchers. The results of this study conclude that there are still media that deliver hoax news, the news delivered is not in accordance with the facts and provocative titles. This can be a boomerang for the news media that conveys the hoax against negative public opinion. So, it is very important for the community not to take it easy and there must be participation from the government in eradicating hoaxes.